2009
DOI: 10.1002/zoo.20243
|View full text |Cite
|
Sign up to set email alerts
|

The influence of captive adolescent male chimpanzees on wounding: management and welfare implications

Abstract: Adolescence, the period lasting from the onset of puberty to the emergence of physical and sexual maturity, is a period of social change for many species including chimpanzees. Several reports have implicitly linked the physiological changes that occur during male chimpanzee adolescence to significant disruption in the social group, which in turn may result in serious agonism and wounding. To assess the association between adolescent males and wounding rates, 38 institutions housing 399 chimpanzees among 59 so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 20 publications
(25 reference statements)
2
40
0
Order By: Relevance
“…226 Such wounding is common in social species and was a significant source of morbidity and mortality among humans in the ancestral environment, and indeed well into the historical period. 227, 228, 229 Given this, it is not surprising that—to quote Firdaus Dhabhar—‘stress perception by the brain may serve as an early warning signal to activate the immune system in preparation for a markedly increased likelihood of subsequent infection'. 230 And although chronic stress is best known to suppress immune function, 231 the types of acute and/or psychosocial stressors most likely to be associated with immediate risk of wounding and hence infection activate both innate and adaptive immunity.…”
Section: Infection Inflammation and Environmental Risk Factors For Mddmentioning
confidence: 99%
“…226 Such wounding is common in social species and was a significant source of morbidity and mortality among humans in the ancestral environment, and indeed well into the historical period. 227, 228, 229 Given this, it is not surprising that—to quote Firdaus Dhabhar—‘stress perception by the brain may serve as an early warning signal to activate the immune system in preparation for a markedly increased likelihood of subsequent infection'. 230 And although chronic stress is best known to suppress immune function, 231 the types of acute and/or psychosocial stressors most likely to be associated with immediate risk of wounding and hence infection activate both innate and adaptive immunity.…”
Section: Infection Inflammation and Environmental Risk Factors For Mddmentioning
confidence: 99%
“…More than 50% of the population is ≤8 yr, and these individuals will be transitioning during the next 15 yr into the adolescent and young adult period (9-19 yr of age), during which they may create some social disharmony. Research in SSP zoos has found that periods of social instability are especially evident in newly formed groups and that wounding is more common in groups that lack strong male leadership (Ross et al 2009). In the current groups in PASA sanctuaries, strong male adult leadership may be rare because the number of adult males in their prime (ca.…”
Section: Discussionmentioning
confidence: 97%
“…Methods for this study were modeled after multi‐institution assessments of wounding in chimpanzees ( Pan troglodytes ; Ross et al, ) and gorillas ( Gorilla gorilla gorilla ; Leeds et al, ). Instructions and training materials were sent to participating institutions.…”
Section: Methodsmentioning
confidence: 99%
“…Ross, Bloomsmith, Bettinger and Wagner () evaluated wounding rates in the entire Association of Zoos and Aquariums (AZA) chimpanzee ( Pan troglodytes ) population. Single‐male groups had higher wounding rates than multi‐male groups.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation